2012
DOI: 10.5021/ad.2012.24.3.348
|View full text |Cite
|
Sign up to set email alerts
|

Type B Pigmentary Demarcation Lines of Pregnancy Involving the Anterior Thighs and Knees

Abstract: Pigmentary demarcation lines are abrupt transition lines between the areas of deeper pigmentation and the areas of lighter, normal pigmentation. Type B pigmentary demarcation lines involve the posterior medial portion of the lower extremities and are more commonly associated with pregnancy. We present a case of pigmentary demarcation lines of pregnancy with erythematous changes, involving both the anterior and posterior aspects of the lower extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In 2012, a case of Type B PDL associated with pregnancy and erythema was reported, in which it also compromised the anterior aspects of the thighs up to the knees. The histological study showed pigmentation in the basal layer and dilation of small vessels with perivascular lymphohistiocytic infiltrate in the upper dermis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, a case of Type B PDL associated with pregnancy and erythema was reported, in which it also compromised the anterior aspects of the thighs up to the knees. The histological study showed pigmentation in the basal layer and dilation of small vessels with perivascular lymphohistiocytic infiltrate in the upper dermis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pregnant women, cases of Type B PDL with erythema have been reported [ 2 , 7 ] and Type B with erythema and involvement of the anterior aspects of the thighs and knees [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Hormonal alterations in the levels of estrogen, progesterone, and melanocyte-stimulating hormone during pregnancy are likely to be involved. [ 4 5 ] Neurogenic inflammation due to trapping of the cutaneous nerves by the enlarging uterus[ 6 ] and genetic factors[ 3 ] may be contributory. Counseling and reassurance is what is generally required owing to the benign and self limiting nature of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pigmentary changes may be perceived aesthetically as unattractive and raise the question of systemic syndromes and diseases . Other considerations include solar protection in lesser pigmented body regions and the possibility of patients unduly focusing on this pigmentary anomaly . PDLs may be particularly troubling when they appear on the face .…”
Section: Introductionmentioning
confidence: 99%